On the obstacles and solutions in the application of Chinese criminal legal aid system - Wang S. (Interactive science, 2016)
the article discovers the problem of application of Chinese legal aid system, which is very low. The problem should be solved as below. The author suggests strengthening the education to investigators, changing the way of employing legal aid lawyers and clarify the content of the right informing and applying for legal aid system. These actions application might well improve the situation.
Keywords: реформа; адвокат; правовая помощь; обязанность уведомления; legal aid system; obligation to notify; reform; legal aid lawyers